FAKTOR SANITASI LINGKUNGAN YANG BERHUBUNGAN DENGAN SKABIES DI PONDOK PESANTREN QOMARUDDIN KABUPATEN GRESIK - Ummu Farihah; R Azizah (Universitas STRADA Indonesia, 2017)
Scabies is the disease of skin infection caused by the infestation and sensitization of mite of Sarcoptes scabiei, many happen in Qor’an schools (Pondok Pesantren) with a fairly high incidence. Environmental sanitation is the factor which is related to the scabies in Qor’an Schools. The aim of this research are to study the environmental sanitation factors which is related to the scabies in Qor’an schools. The sample is 96 students. The screening of scabies and the observation was performed in this research. The result are analyzed by using the chi square test, it’s shows that the place of the provision of clean water is related with scabies in Qor’an schools (p=0.002). The provision of clean water is more potentially in the transmission of scabies than the other. Qor’an schools management expected to improve a bad environmental sanitation factors, especially change the place of the provision of clean water with a single container system.